Non-authentic supplications and its conditions: an analytical study of models in Malaysia - Abdul Ghani Md Din; Ebrahim Mohammed Ahmad Eldesoky; Mohd Azizul Rahman Zabidin; Mohd Zaki Mustafa Masoh (Penerbit Universiti Kebangsaan Malaysia, 2022)
The researchers found that some Muslims made a mistake in practising supplication through some of the literature that we will mention in the research which is due to their use of the non-authentic supplications. Therefore, the research seeks to clarify the conditions for non-authentic supplications so that they are acceptable, especially those whose style is not consistent with the Arabic methods of expression. The research also aims to show that relying on the aforementioned supplications is a safety from error and aggression and a guarantee of acceptance from God Almighty if the conditions and etiquette of supplication are met. The research follows the inductive approach by extrapolating the non-authentic supplications narrated in some heritage books and some contemporary brochures written in Malaysia, as well as the descriptive approach by describing those supplications, analysing them and showing the error in them, correcting them if possible, or rejecting them if they are not acceptable meaning. The research reaches many results, the most important of which are: there are some non-authentic supplications written in the books or brochures but acceptable, and that some of them are not acceptable because they contain unacceptable meanings, and some of them contain a type of aggression in supplication, and that some of them need correction to be accepted. It is hopeful that the authors of the supplication books will know right from wrong and they adhere only to what is correct, and Muslims society will know the errors that may be tainted by some of their supplications and will leave them, and that they should know the meaning of supplication before supplicating with it.